A Review of Egyptian Afforestation Program and its Effect on Agriculture - Subandi , M; Mahmoud, Abdelwahab M; T, Cecep (Asian Journal of Agriculture and Rural Development, 2019)
Egypt has been famous as agricultural country since ancient times. Most Egyptian horticultural and food crop plants are shrubs or small trees with shallow root systems. These plants are susceptible to drought and have a little or no hydrological effect. Egyptian agriculture is mostly dependent on the Nile water (82.59%). Desert areas can be ecologically reclaimed or restored to agronomically productive areas if socioeconomic, cultural, and political factors permit the restoration. Afforestation is when a desert is turned into a woods or forest as a climate change agent and water reservoir. This survey found that Egyptian land was greener than Indonesian land. The availability of the Nile water should be managed as effective as possible to accelerate Egyptian afforestation projects. Egypt may imitate Indonesian success in re-greening the Gunungkidul region of Jogyakarta with the Wanagama forest. The afforestation program affects agricultural practices in Egypt in both the near- and long-term.